Clinical aspects of extensor carpi ulnaris (ECU) injuries in the professional tennis player - Montalvan, B.; Parier, J.; Cousteau, J. P.; le Viet, D. (2001)
Between September 1997 and December 2000, a register was kept of medical consultations at the national coaching centre of the French Tennis Federation (FFT), where the top male and female junior and senior French players train. The results are presented here.